“La lateralidad en el desarrollo de la lectoescritura en el nivel de preparatoria” - Flores Chávez, Joselyn Patricia (2023)
The present research work was carried out with the purpose to diagnose laterality in literacy development at high school level, specifically at Escuela de Educación Básica España, located in Ambato Canton, Tungurahua Province, zone 3. The problem presented by this subject is due to the ignorance of the subject by the teacher about laterality in children, knowing that it still does not have a defined laterality, which implies that children can not a domain body schema and an orientation spatial since this is so important in literacy learning, being a necessary reason to carry out playful activities that help them. The methodology that was used for the investigation is qualitative approach since information was collected on the raised problem and thus be able to propose solutions to the exposed problem, the bibliographic and field design were used where it is based on systematic and in-depth review of the subject, the type of research was descriptive, which allows to know what activities the problem uses with the children, the following techniques are taken into account, the observation sheet was applied to 23 students, 12 boys and 11 girls, allowing a diagnosis in literacy, Therefore, the interview was conducted with the teacher to evaluate their knowledge on the subject, to conclude that laterality is a problem that directly affects literacy learning in children.